Electrostatic and magnetostatic fields for Bessel-Fourier distributed sources on infinite planes - Rosales, M.A.; Ley-Koo, E. (Revista Mexicana de Física E, 2006)
The fields produced by Bessel-Fourier distributions of static electric charges on an infinite plane are constructed by integrating the differential equations for the electrostatic potential and the electric intensity field, subject to the boundary conditions at the source plane. Similarly, the fields produced by Bessel-Fourier distributions of stationary electric currents on an infinite plane are constructed via the integration of the differential equations for the potential and the magnetic induction field, subject to the corresponding boundary conditions.